PERANCANGAN SISTEM INFORMASI AKADEMIK JURUSAN ELEKTORNIKA - Rizki Hardian Sakti; Elfi Tasrif (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
In this modern era today, information technology had become a thing where the society have to be cultivated. The development of information technology was currently running very fast and played an important role in various ways. Computers were one of the important parts in improving information technology. This research aimed to design a tool to be able to assist students in obtaining information in an accurate and effective manner. The design of this information system used the System Development Life Cycle (SDLC) method which was a common methodology in system development and design. System Development Life Cycle (SDLC) had six phases, are namely: identification, initiation and project design, analysis, design, implementation and maintenance. The design carried out were the design and normalization of the database, Entity Relations Diagram (ERD), and system design. The system design had Data Flow Diagram (DFD), Use Case Diagram, Activity Diagram, Sequence Diagram and Class Diagram.Keywords: Information System, System Development Life Cycle, Electonic